\[1)\ |z| + iz = 2 - i\]
\[|x + yi| + i(x + yi) = 2 - i\]
\[\sqrt{x^{2} + y^{2}} + xi + yi^{2} = 2 - i\]
\[\sqrt{x^{2} + y^{2}} - y + xi = 2 - i\]
\[Мнимая\ часть:\]
\[x = - 1.\]
\[Действительная\ часть:\]
\[\sqrt{x^{2} + y^{2}} - y = 2\]
\[\sqrt{1 + y^{2}} = y + 2\]
\[y^{2} + 1 = y^{2} + 4y + 4\]
\[4y = - 3\]
\[y = - \frac{3}{4}.\]
\[Ответ:\ \ z = - 1 - \frac{3}{4}\text{i.}\]
\[2)\ |z| - iz = 3 + 2i\]
\[|x + yi| - i(x + yi) = 3 + 2i\]
\[\sqrt{x^{2} + y^{2}} - xi - yi^{2} = 3 + 2i\]
\[\sqrt{x^{2} + y^{2}} + y - xi = 3 + 2i\]
\[Мнимая\ часть:\]
\[- x = 2\]
\[x = - 2.\]
\[Действительная\ часть:\]
\[\sqrt{x^{2} + y^{2}} + y = 3\]
\[\sqrt{4 + y^{2}} = 3 - y\]
\[y^{2} + 4 = y^{2} - 6y + 9\]
\[6y = 5\]
\[y = \frac{5}{6}.\]
\[Ответ:\ \ z = - 2 + \frac{5}{6}\text{i.}\]